Thermoelectric properties of composite materials based on lead telluride - Matkivskiy, O.M.; Makovyshyn, V.I.; Kupchak, T.I.; Mateik, G.D.; Horichok І.V. (Physics and Chemistry of Solid State, 2022)
The study of composite materials based on mechanical mixtures of microdispersed PbTe and nanodispersed additional component ZnO, TiO2, SiO2 (50-70 nm) or microdispersed CdTe (32-50 μm) was performed. The purpose of this study is to reduce the thermal conductivity of the material. Measurements of specific electrical conductivity, Seebeck coefficient and thermal conductivity coefficient of the studied samples were measured. It is established that the achievement of low values of the thermal conductivity is complicated by the processes of agglomeration of the nanodispersed component at the temperatures of production and processing of composite samples, as well as the chemical interaction of the components of the additive and matrix.